Non-Coding RNA: An Emerging Modulator of ꞵ-Globin Regulation and ꞵ-Hemoglobinopathies (Molecular Medicine Communications, 2022)
ꞵ-Hemoglobinopathies, including ꞵ-thalassemia and sickle cell anemia, are the most common autosomal receiver disorders, globally. Non-coding RNAs (ncRNAs) are derived from exons or introns of protein-coding genes or intronic regions of non-coding genes. There is significant evidence that these ncRNAs may act as protein decoys to impact a variety of biological functions, signaling, transcriptional regulators, cell differentiation, morphogenesis, and developmental regulation. The aberrant regulation of ncRNA expression serves as a hallmark of many hematological disorders, and there is solid evidence that these RNA species can play key roles in the pathogenesis of ꞵ-hemoglobinopathies. In the present review, we provide a summary of recent research findings about the role of ncRNA in globin gene regulation and ꞵ-hemoglobinopathies and their potential as therapeutic targets or prognostic and diagnostic biomarkers.
Keywords: ncRNA; hematopoiesis; ꞵ-thalassemia; sickle cell anemia; fetal hemoglobin; therapeutic targets